The house with chicken legs - Anderson, Sophie (New York : Scholastic Press, 2018)
"All twelve-year-old Marinka wants is a friend. A real friend. Not like her house with chicken legs. Sure, the house can play games like tag and hide-and-seek, but Marinka longs for a human companion. Someone she can talk to and share secrets with. But that's tough when your grandmother is a Yaga, a guardian who guides the dead into the afterlife. It's even harder when you live in a house that wanders all over the world . . . carrying you with it. Even worse, Marinka is being trained to be a Yaga. That means no school, no parties--and no playmates that stick around for more than a day. So when Marinka stumbles across the chance to make a real friend, she breaks all the rules . . . with devastating consequences. Her beloved grandmother mysteriously disappears, and it's up to Marinka to find her--even if it means making a dangerous journey to the afterlife"--Jacket flap.
Bulletin (Center for Children's Books)
Kirkus Starred
School Library Journal starred
Bulletin (Center for Children's Books), September 2018
Kirkus Starred, July 2018
School Library Journal starred, August 2018
Keywords: Friendship -- Juvenile fiction; Future life -- Juvenile fiction; Mediums -- Juvenile fiction; Missing persons -- Juvenile fiction; Friendship -- Fiction; Future life -- Fiction; Mediums -- Fiction; Missing persons -- Fiction